A Broad Spectral Photodetector Using Organic Bisindolo Quinoxaline on ZnO Nanorods - Ming-Hsien Li; Yao-Hong Huang; Chi-Chih Chuang; Sang-Hao Lin; Yi-Hsuan Huang; Chia-Feng Lin; Yung-Sen Lin; Ming-Yu Kuo; Hsiang Chen (Chemosensors, 2023)
Inorganic/organic hybrids of ZnO nanorods (NRs)/bisindolo quinoxaline (BIQ) were fabricated for broadband photosensing applications. Multiple material characterizations revealed the BIQ was self-assembled in a regular form of rod-like domain and an irregular form of amorphous aggregation that were distributed on the ZnO NRs. Optical measurements showed that BIQ can absorb visible light with a wavelength up to 630 nm and effectively generate photoelectrons. Moreover, clustering of BIQ can be observed via the 3D optical microscopy. ZnO/BIQ hybrids were promising for future UV and visible light environmental monitoring applications.